Knowledge, attitude, and practices related to COVID-19 pandemic among social media users in J&K, India - Sabira Aalia Dkhar; Ruqia Quansar; Sheikh Mohd Saleem; S Muhammad Salim Khan (Wolters Kluwer Medknow Publications, 2020)
Background: A series of measures have been suggested to reduce Covid-19 infection, including knowledge training for prevention and control, isolation, disinfection, classified protections at different degrees in infection areas, and protection of confirmed cases. Objectives: We conducted this study with an aim to assess the knowledge, attitude and practice among the general population regarding COVID-19. Methods: This was a cross-sectional study carried out by the Department of Community Medicine, Government Medical College, Srinagar in the month of April 2020. The questionnaire had four segments to collect data regarding social-demographic details, knowledge regarding Covid-19, attitude and practice based questions. The questionnaire was shared via social media applications like face book and Whatsapp to reach the target population. Continuous variables were summarized as frequency and percentage. All the analysis was done using Microsoft Excel 2016. Among participants who responded, 1252 (82%) were in the age group of 18-40 years and 912 (60%) from urban areas. Results: A total of 934 (61%) respondents had heard details on COVID-19 from the social media, 1358 (89%) knew all ways of coronavirus transmission, 602 (40%) felt that COVID-19 is a serious disease, 1184 (78%) responded that they totally agree with the lockdown decision, and 1296 (85%) responded that lockdown is helping in reducing the number of cases. The majority, i.e. 1318 (87%), followed advisories and reported washing hands with soap and water regularly, 1108 (73%) reported regularly wearing masks, 1344 (89%) reported following lockdown guidelines, and 1306 (87%) reported maintaining social distancing. The respondents exhibited good knowledge, positive attitude, and sensible practices regarding COVID-19. Conclusion: Our study showed that the respondents have exhibited good knowledge, positive attitude and sensible practices regarding covid-19 during the pandemic.